A narrativa gráfica em Turma Da Mônica Laços: o fator híbrido mediado pelo literário - Moreira, Elina Monteiro (2021)
The proposed study intends to examine Tumra da Mônica: Laços (2014), a graphic novel published by the imprint GRAPHIC MSP (Graphic Maurício de Sousa Produções), then investigating the relationship between graphic and literary narrative. Undoubtedly, these are independent narratives, with particular formats and distinct genres, and which are of categories that do not have particularly close contact. However, such impressions, although not necessarily wrong, start from a simplified reasoning, from a superficial vision that limits and is incomplete. The research shows that even if the link between the narratives is distant, this factor does not prevent the construction of a link, which in this case is mediated by the hybrid phenomenon and is also found in the intermediality. In a first part, the focus will be concentrated on the literary and its narrative, exploring factors such as its structure and language. The second part deals with establishing the elements of the graphic narrative, ranging from the characteristics to its communication system. On the other hand, the third part of the conversation presentes as its main topic the analysis of Turma da Mônica: Laços (2014), as it was published (and some titles released on the same imprint), also commenting on aspects of the cover and its symbology, the plot and the creative process. Finally, the last part is responsible for tying together the literary and the graphic narrative, bringing to light the hybrid phenomenon and later elaborating on intermediality, and how the two are foundations, functioning as a bridge between these narratives